A case report of gustatory rhinorrhea after maxillectomy performed for Squamous Cell Carcinoma - Zubair, Ujala; Salam, Osama; Haque, Ruda (International Journal of Health Sciences, 2018)
A case of 75 year male presenting with gustatory rhinnorhea since three months. Patient has positive history of maxillectomy performed 4 years back for squamous cell carcinoma of esophagus.